Corpo, interdição e heterotopia: a nudez do corpo da mulher no discurso da propaganda turística oficial brasileira - Pereira, Karoline Machado Freire (2015)
The body of the semi nude Brazilian woman was interdicted in the Brazilian official touristic propaganda, as a way to potentialize the campaigns against the sexual tourism, but this interdiction was not observed in the discourse on Brazilian Carnival, as seen the continuous super exposition of the woman semi nude body in Carnival parades. The general purpose of this dissertation is to analyze the bringing problem, or in other words, to analyze why the nudity of the Brazilian woman body is interdicted in the discourse of the institutional touristic propaganda and the same does not occur in this gender as dealing with Carnival. The specific purposes are: (i) to analyze the action of biopolitical on the body through the meaning effects produced by the relationship between the linguistic and imagetic materialism; (ii) to verify the relationships of power which are established between the revindication, the maintenance, the transformation and the crystallization of identities; (iii) to describe the discursive happenings that helped the changes in the production of knowing the provoked the nudity interdiction of the Brazilian woman body; (iv) to investigate about the disciplinary and control dispositive, above all the interdiction, that act on the body presented in the propagandas; (v) to discuss the intericonicidade (the echoes of the image) in the materiality of the purposed discourse above the perspective of Historical Semiology; (vi) to analyze about the governmentalization in the rules of woman body; (vii) to verify why in the heterotopic space of Carnival the body is not interdicted. As a support to a theoretical foundation, we used the Discourse Analysis (AD), from the ideas of Michel Pêcheux and, above all, the contributions of the works of Michel Foucault, beyond to have a support of the studies realized by Jean-Jacques Courtine on the body and the Historical Semiology of image. Methodologically, the research is characterized as documental and bibliographical, of descriptive and interpretative character. To the corpus analyzing, the arqueogenealogical method of Michel Foucault is used, which is able to dig, of the history, the conditions of possibilities which permit the emergency of discourses, to the analyses of irruption of happenings, of the roles of discursive structures and of ruptures in the memory nets. The corpus is composed by thirty official touristic propagandas of Brazil produced by Brazilian Institute of Tourism (EMBRATUR), in a time memory that goes from the decade of 1970 till the year of 2015. In the results of the research, it was verified that the Carnival is a heterotopic space of passage, due this the nudity is permitted in time and in Carnival space, this is, the systems of control, above all the interdiction, that over whelm every rule of diary life, are revoked during the Carnival, and this permitting holds, inclusive, the discourse of Brazilian official touristic propaganda.